Taxonomic studies in the Schizymeniaceae (Nemastomatales, Rhodophyta): on the identity of Schizymenia sp. in the Azores and the generic placement of Nemastoma confusum - Gabriel, Daniela (2013)
Copyright © 2011 International Phycological Society.